Narratives of rebellion - Joosse, Paul (European journal of criminology, 2021)
Working from a narrative criminological framework, this article distinguishes and describes the ‘narrative of rebellion’ as a generic form that can be encountered widely in situations of asymmetrical struggle. Because narratives of rebellion furnish their tellers with agentic potential across various stages of the ‘rebellious career’ (from contemplation, to participation, to capture, and ultimately to peril), they are desirable cultural accoutrements for bringing into seditious struggle. Rebellion stories typically (a) subsume individuals within collective avatars that are represented as existing somehow ‘outside of life’ – often through legendary martyrdom, (b) advance plots that draw causal connections between failure/death and regenerative proliferation ‘from below,’ and (c) promulgate of a sense of solidarity with many as-yet unseen fellow travelers. These features offer protective resources for rebels engaging in criminal resistance, while also providing a framework for sense-making that, rather than obfuscating danger (a prominent feature of existing theories of rebellious participation), offers interpretive resources for contending with the likelihood of a perilous fate.